Impact of childhood household support on depression and self-reported mental and physical health - Oluwasegun Akinyemi; Mojisola Fasokun; Fadeke Ogunyankin; Raolat Adenike Salami; Ifunanya Stella Osondu; Akachukwu Eze; Kakra Hughes; Miriam Michael; Temitope Ogundare (PLoS ONE, 2025)
Background Perceived household support during childhood defined as the presence of an adult who consistently tried to ensure that basic needs were met has lasting effects on mental and physical health across the life course. While its protective role is well recognized, less is known about whether these associations vary across gender and racial/ethnic groups. Methods We conducted a cross-sectional analysis of 31,233 U.S. adults from the 2021–2024 Behavioral Risk Factor Surveillance System (BRFSS). The primary exposure was self-reported childhood household support, categorized as “Never,” “A Little of the Time,” “Some of the Time,” “Most of the Time,” or “All of the Time.” Outcomes included lifetime diagnosis of depression, average monthly poor mental health days, and poor physical health days. Analyses used inverse probability weighting and survey-adjusted regression, controlling for sociodemographic characteristics, state, year, and month fixed effects. Models were stratified by gender and race/ethnicity to evaluate moderating effects. Results Among respondents (mean age 52.2 years; 63.4% female; 76.0% White), Individuals who reported “Never” being supported were 19.4 percentage points more likely to report a depression diagnosis (95% CI, 11.6–27.2), experienced 5.33 more poor mental health days (95% CI, 3.64–7.03), and 2.77 more poor physical health days (95% CI, 1.23–4.32) per month compared to those “Always” supported. A clear dose–response gradient was observed across all categories of support. Gender-stratified analyses revealed that women had consistently higher adjusted probabilities of depression than men across most support categories. Race/ethnicity-stratified analyses indicated that Black respondents consistently exhibited lower adjusted probabilities of depression compared with White respondents, while Hispanic respondents reported more poor mental health days in the “A little of the time” category. Conclusions Perceived childhood household support is strongly and progressively protective against depression and poor mental and physical health outcomes in adulthood. However, its benefits are not uniformly distributed: women remain disproportionately vulnerable to depressive outcomes even with partial support, while race/ethnicity-specific differences suggest the presence of resilience as well as distinct vulnerabilities. These findings highlight the universal importance of stable, supportive caregiving environments and underscore the need for prevention and intervention strategies that are both gender-sensitive and culturally tailored to reduce lifelong health disparities.